Manfaat Shalat untuk Kesehatan Mental: Sebuah Pendekatan Psikoreligi Terhadap Pasien Muslim - Safiruddin Al Baqi; Abdah Munfaridatus Sholihah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2019)
Islam is one of the largest religions in the world, which means that many of the world's population adheres to Islam. From the large number of Muslims, it urges practitioners of psychology or mental health to provide services that are appropriate for Muslims. The therapeutic approach as a psychological service for Muslims can be done with a religious (psychological) approach, especially with their religious practices. Shalat or prayer in Islam is one of the practices of worship that is able to generate many benefits psychologically for Muslims who carry it out, including relieving stress, increasing subjective well-being and interpersonal sensitivity. Finally, shalat can be an alternative psychotherapy for Muslim patients as a therapeutic process which helps improve his mental health. This paper aims to unite (integrate) religiosity and psychotherapy. Keywords: Islam, prayer, mental health, psycho-religious approach, shalat.